The effects of supplementing Napier grass (Pennisetum purpureum) with rock phosphate and steamed bone meal compared with a commercial mineral mix on phosphorus absorption in cattle - Odongo, N.E.; Tanner, J.C.; Romney, Dannie L.; Plaizier, J.; Straaten, P. van; McBride, B. (Springer, 2002)
Twelve Boran steers with a mean live weight of 215.8 ± 13.9 kg were used in an incomplete Latin Square experiment to compare the apparent phosphorus (P) absorption in cattle when Napier grass (Pennisetum purpureum) was supplemented with Busumbu rock phosphate (BRP), Minjingu rock phosphate (MRP), steamed bone meal (SBM) or a commercial mineral mix (CMM). The steers were housed individually and supplemented with P at 0, 4.5 or 17.5 g P/day. Dry matter intake (DMI) and dry matter digestibility (DMD) were not affected (p > 0.05) by the source of Live weight gains (LWG) were different (p < 0.05) across the sources of The coefficient for apparent P absorption from the supplement (CAPA), DMD and LWG decreased linearly (p < 0.05) with period. Dry matter intakes were not significantly different (p > 0.05) across periods. The level of P supplementation had no significant effect (p>0.05) on DMI or LWG. However, increasing the level of P supplementation significantly increased (p < 0.05) the DMD of the basal diet. There was also a significant (p < 0.05) source X level interaction for CAPA. The CMM had the highest CAPA, which decreased from 106% to 74.7'0 with increasing level of P supplementation. For SBM, BRP and MRP, increasing P supplementation also increased CAPA. The CAPA for SBM and BRP and BRP and MRP were not significantly (p>0.05) different from each other. These results suggest that BRP has potential as a source of P for ruminants.